Price Structure in Two-sided Markets: Evidence from the Magazine Industry? - Ulrich Kaiser; Julian Wright (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
We present and estimate a model of competition in a two-sided market: the market for magazine readership and advertising. Using data on magazines in Germany, we find evidence that magazines have properties of two-sided markets. The results are consistent with the perception that prices for readers are "subsidized" and magazines make most of their money from advertisers. Consistent with advertisers valuing readers more than readers value advertisements, our results imply that higher demand or lower costs on the reader side increase ad rates, but that higher demand or lower costs on the advertising side decrease cover prices.
Keywords: 330; Zeitschrift; Markt; Zeitungswerbung; Deutschland